2019
DOI: 10.1063/1.5049713
|View full text |Cite
|
Sign up to set email alerts
|

Significant thermal conductivity reduction of CVD graphene with relatively low hole densities fabricated by focused ion beam processing

Abstract: The detrimental effect of nanoscale hole defects on the in-plane thermal conductivity (k) was first examined for supported CVD graphene. A focused ion beam punctured equally spaced 50-nm diameter holes with different hole spacings (200, 400, and 800 nm) in supported graphene on an 8-nm thin SiO2 substrate. For the relatively low 4.91% porosity, the thermal conductivity showed a significant reduction to 212.6 W/mK from 1045 W/mK in supported graphene with no holes and even more dramatically so from 3500 W/mK in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The results reveal that the κ eff decreases dramatically with the increasing porosity, which is consistent with experimental results. 16,55 Normally, the GFs have a density in the 1.9−2.15 g/cm 3 range, corresponding to porosity in the 5.12−16.15% range. To control the effect of irrelevant variables, the porosity of the modeling was set to 10% in this section.…”
Section: Finite Element Resultsmentioning
confidence: 99%
“…The results reveal that the κ eff decreases dramatically with the increasing porosity, which is consistent with experimental results. 16,55 Normally, the GFs have a density in the 1.9−2.15 g/cm 3 range, corresponding to porosity in the 5.12−16.15% range. To control the effect of irrelevant variables, the porosity of the modeling was set to 10% in this section.…”
Section: Finite Element Resultsmentioning
confidence: 99%
“…Nevertheless, the desired functionality of graphene in a wide range of fields is gained when graphene is combined with another class of materials, resulting in the formation of composite materials with improved properties . The recent investigations of hole transport layers suggest a new class of materials for modification of graphene properties with aim of application in optoelectronics . Particularly, heterostructures made of graphene and thin transition metal oxide (TMO) films seem to be very attractive in optoelectronics and may play the role of hole or electron injection layers (HIL/EIL) .…”
Section: Introductionmentioning
confidence: 99%
“…It is experimentally demonstrated that the grain boundaries effects from grain sizes [25,26] and grain misorientation [27,70] significantly influence on the thermal conductivity of graphene using the opto-thermal Raman method. Recently, various types of graphene such as doped graphene [11,28], hole defected graphene [30,31] and graphene with vacancies [32,33] have been produced and the opto-thermal Raman technique has revealed the modified graphene exhibits the reduced thermal conductivity compared to pristine graphene. Likewise, graphene will be further structurally modified to alter its unique properties and the opto-thermal Raman thermometry will act as a useful tool for estimating the altered thermal properties of graphene.…”
Section: Opto-thermal Raman Thermometrymentioning
confidence: 99%
“…With those techniques, volumetric papers regarding thermal properties of graphene were reported. However, the characterization of thermal properties of graphene is still important since many researches nowadays focus on controlling the thermal conductivity of graphene [24] by inducing defects such as grain boundaries [25][26][27], dopants [11,28,29], holes [30,31] and vacancies [32,33]. Thus, a thorough examination on the altered thermal properties of graphene is necessary to elaborate the effect of induced defects.…”
Section: Introductionmentioning
confidence: 99%